Atividade antimicrobiana do óleo essencial de Zingiber officinale sobre bactéria periodontopatogênica (Klebsiella pneumoniae) em resina composta convencional e bulk fill - Silva, André Rodrigo Justino da (2025)
Dysbiotic biofilm is the primary etiological factor in periodontal disease, and its complex composition may involve significant participation of the gram-negative bacterium Klebsiella pneumoniae. Natural products, such as Zingiber officinale, have proven antimicrobial activity, but it has been little tested against K. pneumoniae. Thus, the aim of this study was to verify the cytotoxicity, antimicrobial and anti-adherent activity of Zingiber officinale essential oil against Klebsiella pneumoniae on smooth surfaces of human enamel and Tetric N-Ceram Bulk-fill and Filtek Z350 XT resins. The experiments were performed by the same operator in triplicate, with cytotoxic profile tests of the compound in three blood types; determination of the minimum inhibitory concentration, minimum bactericidal concentration, and minimum adhesion inhibitory concentration in six ATCC strains of Klebsiella pneumoniae; and antimicrobial and anti-adherent activity tests on twelve specimens of each material tested, for quantification of colony-forming units. The results showed that ginger is not toxic to human cells, exhibiting bactericidal and bacteriostatic action at a concentration of 500 µl/ml, and a minimum inhibitory adhesion concentration of 12.5 µl. In the test specimens, ginger showed antimicrobial activity on human enamel and antimicrobial and anti-adherent activity on Tetric N-Ceram Bulk-fill resin, unlike Filtek Z350 XT resin, where ginger was ineffective. Thus, Zingiber officinale has bactericidal, bacteriostatic, and anti-adherent action against Klebsiella pneumoniae and inhibits its growth and adhesion to the tested bulk-fill resin, and also inhibits growth on human enamel.